The Influence Of Job Insecurity On Job Stress In Chemical Employees - Fachriany, Amelia (Psikologi Prima, 2025)
The work environment is the place where employees work and can be a force that directly or indirectly affects employee performance. Employees who work in the chemical industry are certainly directly related to chemicals as the core of the work. Each chemical will affect individual health and also the surrounding environment. Poor environmental conditions will cause work stress in employees. One of the triggers of stress at work is a high sense of job insecurity. This study aims to investigate the impact of job insecurity on job stress among chemical employees. The sampling technique employed was non-probability sampling, specifically purposive sampling. The total population in this study amounted to 159 employees. This study uses the Multidimensional Qualitative Job Insecurity Scale (MQJIS) and Job Stress Scale (JSS). Data analysis techniques in this study using simple regression tests with the help of SPSS software version 26.0 for Windows. The results of this study show indicate a very significant positive influence between job insecurity and job stress among chemical employees, with a significance value of 0.000 (p < 0.01). Moreover, job insecurity has an influence of 72.3% on job stress, and other factors outside the scope of this study influence the remaining 27.7%.